“A constant battle against sedentary lifestyle and screen time”: Swedish school nurses' views on school children's physical activity and its promotion - a grounded theory study - Wiklund, Emelie; Wiklund, Maria; Vikman, Jenny; Hedenborg, Susanna (Frontiers in Sports and Active Living, 2024)
School nurses are in a key position to promote children's physical activity. They engage all children in health dialogues and use different approaches to inform children about physical activity and motivate them to change their physical activity level. In a school context, it is important to explore and problematize school nurses' views of children's physical activity and the influence of these views on their professional practice in the school health service.Identifying and problematizing school nurses' views of physical activity would enable them to create improved guidelines and equivalent ways of working in the future. Therefore, this study aims to discursively explore Swedish school nurses' views on school children's physical activity and its promotion and elucidate them through a discursive framework based on sensitizing concepts. This study uses a qualitative research design with a constructivist grounded theory approach. Semi-structured interviews were conducted with 24 school nurses.The analysis resulted in a core category describing how school nurses use intertwined views to lead children from sedentarity to physical activity. Furthermore, the school nurses' practices were identified in three categories: fostering everyday movement as a tool for health, battling children's sedentarity under difficult conditions, and promoting everyday movement and compensating for unequal access. The results indicate that school nurses lack common and clear guidelines for their mission to promote physical activity to children, which may lead to inequality in access to physical activity for children and young people.